Nucleation of recrystallisation in castings of single crystal Ni-based superalloys - Mathur, H; Panwisawas, C; Jones, C; Reed, R; Rae, C (Elsevier, 2017)
Recrystallisation in single crystal Ni-based superalloys during solution heat treatment results in a significant cost to the investment casting industry. In this paper two sources of surface nucleation have been identified in the alloy CMSX-4®. Firstly, Electron Backscattered Diffraction (EBSD) has revealed micro-grains of γ', between 2 and 30 μm diameter in the layer of surface eutectic found in the upper part of the casting. These have high angle boundaries with respect to the bulk single crystal and a fraction coarsen during solution heat treatment. Secondly, in the lower regions where surface eutectic does not form, locally deformed regions, 5–20 μm deep, form where the metal adheres to the mould. The local strain causes misorientations up to ≈20° with respect the bulk single crystal, and after heat treatment these regions develop into small grains of similar low-angle misorientations. However, they also form twins to produce further grains which have mobile high-angle boundaries with respect to the bulk single crystal. Experiments have shown that micro-grains at the surface grow to cause full recrystallisation where there is sufficient strain in the bulk material, and by removing these surface defects, recrystallisation can be completely mitigated. Etching of the cast surface is demonstrated to be an effective method of achieving this.